DETERMINANTS OF INTEREST IN USING E-WALLETS IN TRANSACTIONS BETWEEN MUSLIM TRADERS AND CONSUMERS: FINANCIAL LITERACY, PERCEPTION OF EASE AND PERCEPTION OF RISK: (CASE STUDY IN THE TRADITIONAL MARKETS OF PEKALONGAN CITY) - Weni Novia Lestari; Mohammad Rosyada (Institut Agama Islam Negeri (IAIN) Bone, 2026)
This study aims to analyze the influence of financial literacy, perceived ease of use, and perceived risk on the interest in using e-wallets in transactions between Muslim traders and consumers in traditional markets in Pekalongan City. This quantitative study used a questionnaire as a data collection instrument with a sample of 96 respondents taken using a purposive sampling technique. The collected data were then processed using Eviews. The results showed that financial literacy had a positive and significant influence on the interest in using e-wallets. However, perceived ease and perceived risk do not influence interest in using e-wallets. However, simultaneously, financial literacy, perceived ease of use, and perceived risk had a significant influence on the interest in using e-wallets